Credit Constraints and Job Mobility - Hagstrom, Paul A.; Owen, Ann L. (Journal of Income Distribution®, 2008)
We estimate the probability of voluntary job change using datafrom the Panel Study of Income Dynamics (PSID) and imputed valuesfor several different measures of financial stress from the Surveyof Consumer Finances (SCF). Our main finding is that single men aremore likely to respond to credit constraints by voluntarily switchingjobs. For married men, the effect depends on the type of financialstress experienced. Our results suggest that the higher rate of job mobilityamong single men can be attributed to both higher incidence ofcredit constraints among this group as well as a differential responseto these constraints.